'And Truth—So Manifold!'—Transfeminist Entanglements. (September 2013) - Keller, Catherine
How are we theologically imagining feminism's further becomings at this juncture of multiple intertwined uncertainties? Aided by a poem by Emily Dickinson, this meditation on a transfeminist (not postfeminist) potentiality within and beyond Christianity plies a trinity of entanglement (relationality), mystery (apophasis), and multiplicity (polydoxy).